Unvieling Media Narratives in Promoting Gender Equity in Islamic PERSIS Education - Komariah, Siti; Asyahidda, Fajar Nugraha; Wilodati, Wilodati (The Journal of Society and Media, 2024)
In the modern world, communication through media and digital channels has become increasingly prevalent. It is imperative to consider how these channels influence social perceptions and constructs. Gender equity is a critical topic in educational contexts. A comprehensive study was conducted to analyze the portrayal of gender constructs in media narratives and their impact on gender equity in Islamic PERSIS educational environments. The study utilized qualitative research, including content analysis of media narratives and interviews with members of Islamic PERSIS organizations. The study brings to light the positive and negative roles of media narratives in shaping attitudes and perceptions about gender roles. Therefore, the study emphasizes the need to examine media representations to promote gender equity critically. The research has significant implications for contemporary media and digital communication in advancing gender equity in educational settings related to Islamic PERSIS organizations. It encourages a more responsible approach to media content creation by acknowledging the power of media narratives to shape perceptions. This contributes to a broader conversation about gender equity and the role of contemporary media in promoting social change and inclusivity